Vehicle miles traveled fee to complement the gas tax and mitigate the local transportation finance deficit. Issue 1 (1st January 2021) - Rodriguez, Agustin; Pulugurtha, Srinivas
ABSTRACT: The objective of this research is to gather data for an urban area, evaluate, and assess the applicability of vehicle miles traveled (VMT) fee to replace or complement the gas tax, and mitigate the local transportation finance deficit. Vehicle data collected from three geographically distributed service stations in Charlotte, North Carolina were used to evaluate multiple VMT fee scenarios. The results indicate that charging 0.625 cents per each mile traveled or 1.00 cent per additional mile exceeding 5, 000 miles per year, to complement the gas tax, could generate enough revenue to mitigate the transportation finance deficit estimated equal to $30 M to $35 M at the time of this research for the city of Charlotte, North Carolina. Furthermore, this research explored the gross vehicle weight (GVW) as a factor to account for pavement deterioration, emissions, and the effect of heavier vehicles on travel time and safety for charging vehicle owners. The cost to implement the recommended VMT fee is minimal, the driver's privacy is protected, and the VMT fee is less than $100 per year per vehicle for over 75% of the vehicle owners in the urban area.